Escrita de fanfics e a constituição do sujeito autor no ensino médio : movimentos dialógicos com contos de Machado de Assis - Couto, Regiani Leal Dalla Martha (2024)
Based on the premise that the cultural acts of reading and writing are indissociable and are organized into an architectural whole, we guided our research by taking as our main point the authorship of high school students when writing fanfics based on Machado de Assis’ short stories. We believe that the literary text contains different possibilities for the constitution of meanings, making it a fruitful target for dialogue and interaction. In this way, our objectives were to investigate how the student becomes an author in the architectural process from reading Machado’s short stories to writing fanfics and to analyze how the student appropriates Machado’s short stories and responds actively, considering the dialogical movements between the 19th century and the contemporaneity. To achieve these presuppositions, we organized a reading and writing workshop, considering the concepts of authorship, architectonics and chronotope engendered by Bakhtin (2011, 2018), as well as the notion of dialogic relations (Bakhtin 2018, Brait, 2018). Following a dialogic perspective, with a qualitative approach, we developed our DDP – Dialogic Didactic Practice – with students from the Integrated High School Technical Courses at the Federal Institute of Rondônia, Ji-Paraná Campus, who were able to value Machado’s short stories and present their active creative responses through writing. This dialog between enunciations and subjectivities, observing different contexts, was crucial for the students to constitute meanings and present a responsive comprehension. We believe that reading Machado’s short stories as motivation for writing fanfics encouraged the authorship of high school students, since the participants understood reading and writing as an interconnected process, recognized as a totality promoted by interaction. In our analysis, we noticed echoes of the students' voices when they commented “Machado only brings good gossip”, “Machado leaves unknowns for the reader”. In addition, when we analyzed the fanfic genre, considering the architectonics as a process that unites form, material and content, we evidenced, through the collation, the dialogues, proximities and distances established with the Brazilian author, thus becoming perceptible the subjects' evaluative positions when assuming their authorial roles.